MOSFE-Capacitor Silicon Carbide-Based Hydrogen Gas Sensors - Artur Litvinov; Maya Etrekova; Boris Podlepetsky; Nikolay Samotaev; Konstantin Oblov; Alexey Afanasyev; Vladimir Ilyin (Sensors, 2023)
The features of the wide band gap SiC semiconductor use in the capacitive MOSFE sensors’ structure in terms of the hydrogen gas sensitivity effect, the response speed, and the measuring signals’ optimal parameters are studied. Sensors in a high-temperature ceramic housing with the Me/Ta2O5/SiCn+/4H-SiC structures and two types of gas-sensitive electrodes were made: Palladium and Platinum. The effectiveness of using Platinum as an alternative to Palladium in the MOSFE-Capacitor (MOSFEC) gas sensors’ high-temperature design is evaluated. It is shown that, compared with Silicon, the use of Silicon Carbide increases the response rate, while maintaining the sensors’ high hydrogen sensitivity. The operating temperature and test signal frequency influence for measuring the sensor’s capacitance on the sensitivity to H2 have been studied.